The effects of load and training pattern on acute neuromuscular responses in the upper body - Robbins, D. W.; Goodale, T. L.; Docherty, D.; Behm, D. G.; Tran, Q. T. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine the effects of repetition maximum (RM) loads and training patterns on acute neuromuscular responses in the upper body. Markers of fatigue were monitored under a descending pattern (DP), in which repetitions decreased in subsequent sets, and an ascending pattern (AP), in which repetitions increased in subsequent sets. Both training patterns were performed using 5- and 10-RM loads. Fatigue was assessed by monitoring changes in force output, motor unit activation and muscle twitch characteristics (peak twitch [PT], time to PT [TPT], and ½ relaxation time [RT]). All 4 protocols (5-RM DP, 5-RM AP, 10-RM DP, and 10-RM AP) produced significant decreases pre to postprotocol in force output, TPT, and½RT. With the exception of 5-RM DP, all protocols produced significant decreases in motor unit activation. Pre to postprotocol, PT forces were potentiated under 5-RM loads, whereas they were depressed under 10-RM loads. Hence, a main effect for training protocols showed that changes in PT force were significantly different under 5-RM, as compared to 10-RM loads. The results indicate that central fatigue may be independent of load and pattern, whereas peripheral fatigue would appear to be dependent on load but not pattern.